POSTMODERNISM: DESCRIPTIVE PRACTICES OF CULTURAL REFLECTION - Olena Yatsenko (Освітній дискурс, 2020)
The problem of discreteness and continuity of time and space correlates with the problem of the whole and the general. If ontology is presented as a world of individual things, and metaphysical systems describe the world as a whole, then the philosophy of postmodernism questions and criticizes classical examples of the postulation of integrity. The result of such a worldview disposition is an existential-horizontal vector of goal-setting and expediency as such. The development, or rather, the "habitation" of space in time occurs as its marking - the establishment of marks, leaving traces and cartography. All the monumentality of culture is, thus, a sign-symbolic system that reformats the world in a human-sized format. The temporality of subjectivity is not only an existential tragedy, but also a sacred gift of an essential vision of things and phenomena. Even if in postmodernism this sacredness is legitimized by society and culture, not by the eternity of the universe.